Perubahan Karakteristik Kimia dan Mikrobiologis Jruek Drien (Durian Fermentasi Khas Aceh) selama Fermentasi - Murna Muzaifa; Ryan Moulana; Yuliani Aisyah; Zainuddin Zainuddin; Faidha Rahmi (Jurnal Teknologi dan Industri Pertanian Indonesia, 2018)
Jruek drien is one of traditional fermented food of Aceh. This product made from flash of durio that fermented without starter addition. Explorative research has been conducted to examine the change of chemical and microbiological characteristics of jruek drien during fermentation. This study used completely randomized design with single factor (length of fermentation: 1,3,5 and 7 days). The parameters analyzed were water content, pH, total acid, total sugars, total lactic acid bacteria and yeast. The results showed that water content and acid total were increased while pH and sugar content were decreased. The highest total of lactic acid bacteria was found on day 3. Yeast detected only on early fermentation and no detected on 7th day.